Internalisasi Nilai-Nilai Agama Dalam Pai Untuk Menanggulangi Kenakalan Remaja Pada Sekolah Umum (Studi Multi Situs di SMP Negeri 9 dan SMP Swasta Kartika IV-8 Malang) - Fauzi, Ahmad (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2017)
Embedded in students as a result of society quickly accepting it without filtering it. This leads to the widespread deviation perpetrated by today's teenagers. This study aims to describe clearly inculcating religious values in Islamic religious education to cope with juvenile delinquency in public schools (multisite studies in SMP Negeri 9 and SMK Swasta Kartika IV-8 Malang). The focus of this research is 1). What are the factors that become the cause of juvenile delinquency in SMP Negeri 9 Malang and SMK Swasta Kartika IV-8 Malang 2)? How to Process Internalization of Religious Values ​​In PAI to Tackle Juvenile Delinquency At Public Schools in SMP Negeri 9 Malang and Private Junior High School Kartika IV-8 Malang.The conclusions of this research are: 1) Factors That Become Causes of Juvenile Delinquency in Junior High School 9 Malang and Private Junior High School Kartika IV-8 Malang are: a) Lack of discipline in the child. b) Low motivation to learn. c) Lack of attention of parents to their children. d) Lack of parents in modeling their children. e) Lack of religious education within the family. f) The influence of the environment around the school. g) School failure in shaping character. 2) Internalization Process of Religious Values ​​In PAI to Tackle Juvenile Delinquency in Public Schools at SMP Negeri 9 Malang and Junior High School Private Kartika IV-8 Malang are: a) Transformation of religious values: (1) Develop K-13 (2) counseling and guidance of all parties. b) Transaction of religious values: (1) Culture 3 S (2) exemplary teachers (3) customs of religious culture (4) PAI teacher collaboration and KKN teachers. c) Transinternalization of religious values: (1) lack of violation of students (2) sense of student responsibility (3) awareness of students not to commit juvenile delinquency. Keywords: Internalization, Religious Values, Juvenile Delinquency